2014
DOI: 10.1534/g3.114.011056
|View full text |Cite
|
Sign up to set email alerts
|

Pattern of Mutation Rates in the Germline of Drosophila melanogaster Males from a Large-Scale Mutation Screening Experiment

Abstract: The sperm or eggs of sexual organisms go through a series of cell divisions from the fertilized egg; mutations can occur at each division. Mutations in the lineage of cells leading to the sperm or eggs are of particular importance because many such mutations may be shared by somatic tissues and also may be inherited, thus having a lasting consequence. For decades, little has been known about the pattern of the mutation rates along the germline development. Recently it was shown from a small portion of data tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(30 citation statements)
references
References 24 publications
2
28
0
Order By: Relevance
“…It is likely that some of these substitutions would result in inviable offspring and would never be observed in an adult population. Our result suggests that mutational load varies between different cell divisions, consistent with previous work that suggests a variable lesion rate between cell types (Gao et al, 2011, 2014). Mutational load is the net product of damage and repair, and further characterization of how lesions occur and accumulate in the germline is needed to better understand the evolutionary ramifications of this process (Moorjani et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…It is likely that some of these substitutions would result in inviable offspring and would never be observed in an adult population. Our result suggests that mutational load varies between different cell divisions, consistent with previous work that suggests a variable lesion rate between cell types (Gao et al, 2011, 2014). Mutational load is the net product of damage and repair, and further characterization of how lesions occur and accumulate in the germline is needed to better understand the evolutionary ramifications of this process (Moorjani et al, 2016).…”
Section: Discussionsupporting
confidence: 92%
“…Sun & D. Hedgecock, unpublished data), active transposable elements (see below), and the large number and potential clustering of mutations arising during premeiotic cell divisions (Klekowski & Godfrey ; Gao et al . , ). The importance of premeiotic cell divisions for mutation accumulation is illustrated by molecular evidence for male‐driven evolution in mammals and birds, in which males have three‐ to six‐fold higher mutation rates than females (Ellegren & Fridolfsson ; Nachman & Crowell ; Makova & Li ).…”
Section: Discussionmentioning
confidence: 99%
“…Classical, mutation-drift, equilibrium theory, however, may overestimate the lethal mutation rate necessary to support the observed mutational load, because marine populations may be far from demographic and genetic equilibria, owing to variability in recruitment (Hjort 1914;Fogarty et al 1991;Cushing 1996;Myers 2001;Houde 2008) and sweepstakes reproductive processes (Hedgecock & Pudovkin 2011), in which a relatively small fraction of the spawning population may be responsible for the bulk of recruitment. Some features of oyster population biology that could increase the load but not necessarily the rate of lethal mutations or that could increase the variance in or initial frequency of lethal mutations include sweepstakes reproductive success, low effective population size (N e~1 50; Hedgecock 1994, Li & Hedgecock 1998, active trans-posable elements (see below), and the large number and potential clustering of mutations arising during premeiotic cell divisions (Klekowski & Godfrey 1989;Gao et al 2011Gao et al , 2014. The importance of premeiotic cell divisions for mutation accumulation is illustrated by molecular evidence for male-driven evolution in mammals and birds, in which males have three-to six-fold higher mutation rates than females (Ellegren & Fridolfsson 1997;Nachman & Crowell 2000;Makova & Li 2002).…”
Section: Population Genetics Of Deleterious Mutations In the Pacific mentioning
confidence: 99%
“…This advance might extend the application of Galton-Watson models and sampling results to other contexts in biology, such as population genetics or the emergence of mutations in model organisms that can be experimentally assayed. 29 We also developed an interesting result concerning the analysis of stochastic proportions. We showed that sampling a rare particle updates the expected proportion of that rare particle to the value determined by the size-biased distribution of the proportion.…”
Section: Discussionmentioning
confidence: 99%